“Health aspects of physical and sports activities in schools” A field study of facilities and spaces in the province of M’Sila for secondary education - Bendkfal, rachid (sports creativity, 2025)
Physical and athletic activity at school is considered a building block for the psychological, social, educational, and moral development of the individual in general, as it distinguishes itself from other subjects in that it meets the psychological needs of students through play and their social needs through peer groups of friends and classmates. However, all this can only be achieved through the actual and healthy practice of the activity, which is what we address in this paper under the general question: “Is there a healthy practice of physical and sports activities in schools in terms of structures and spaces?” The secondary schools of the province of M'Sila were used as a model. The study concluded with the following results: - Assessing the reality of physical and athletic activity in the province of M'Sila. - Achieving the health objectives of physical and athletic activity in schools, for which secondary schools were used as a sample, as they are currently far from these objectives. - Despite the existence of laws and regulations that allow students to practice this activity, there is no actual practice in the true sense of the word. - Often, spaces and structures play a negative role by causing injuries to students. - The need to review the policy of adaptation with regard to structures and spaces, taking into account the principle of safety for students.